Influence of poultry litter and plant density on the production and chemical composition of the essential oil of Schinus terebinthifolius Raddi fruits - Tabaldi,L.A. (2014)
The aim of this study was to evaluate the production and chemical composition of the essential oil of Brazilian pepper fruits grown in single and double rows using different doses of semi decomposed poultry litter in two evaluation times. The experiment was carried out at the Federal University of Grande Dourados, in the city of Dourados, state o- Mato Grosso do Sul, Brazil, from October 2009 to November 2010. Brazilian pepper plants were grown in single and double rows in soil with incorporated poultry litter at the doses of 0, 5, 10, 15 and 20 t ha-1. Treatments were arranged as a 2 x 5 factorial experiment in a randomized block design with four replications. Fruits were harvested 180 and 390 days after transplant (DAT). There was a significant interaction for fresh weight of fruits and weight of 50 fruits, being the values higher at 180 DAT in the double rows with increasing poultry litter doses. Fruits harvested 390 DAT showed higher diameter compared with those harvested 180 DAT. The number of fruits per bunch was significantly influenced by the doses of poultry litter, presenting a linear increase with increasing doses. The essential oil of the Brazilian pepper fruits obtained by hydrodistillation and analyzed by Gas chromatography - mass spectrometry exhibited predominance of monoterpenes, highlighting α-pinene (20.14%) as the major constituent. The chemical composition of the essential oil was not influenced by the number of plant rows in the plot or by the doses of poultry litter in any evaluation time. Therefore, the cultivation of Brazilian pepper plants is recommended in double rows, with 13.59 t ha-1 of incorporated poultry litter in the soi, and with harvest of 180 DAT for higher fruit production.